Schisandrin A from Schisandra chinensis Attenuates Ferroptosis and NLRP3 Inflammasome-Mediated Pyroptosis in Diabetic Nephropathy through Mitochondrial Damage by AdipoR1 Ubiquitination. (11th August 2022) - Wang, Xiaohu; Li, Qin; Sui, Bangzhi; Xu, Maodi; Pu, Zhichen; Qiu, Teng
Abstract : Schisandra chinensis, as a Chinese functional food, is rich in unsaturated fatty acids, minerals, vitamins, and proteins. Hence, this study was intended to elucidate the effects and biological mechanism of Schisandrin A from Schisandra chinensis in DN. C57BL/6 mice were fed with a high-fat diet and then injected with streptozotocin (STZ). Human renal glomerular endothelial cells were stimulated with 20 mmol/L d-glucose for DN model. Schisandrin A presented acute kidney injury in mice of DN. Schisandrin A reduced oxidative stress and inflammation in model of DN. Schisandrin A reduced high glucose-induced ferroptosis and reactive oxygen species (ROS-)-mediated pyroptosis by mitochondrial damage in model of DN. Schisandrin A directly targeted AdipoR1 protein and reduced LPS+ATP-induced AdipoR1 ubiquitination in vitro model. Schisandrin A activated AdipoR1/AMPK signaling pathway and suppressed TXNIP/NLRP3 signaling pathway in vivo and in vitro model of DN. Conclusively, our study revealed that Schisandrin A from Schisandra chinensis attenuates ferroptosis and NLRP3 inflammasome-mediated pyroptosis in DN by AdipoR1/AMPK-ROS/mitochondrial damage. Schisandrin A is a possible therapeutic option for DN or other diabetes.